Linear DNAs Concatemerize in Vivo and Result in Sustained Transgene Expression in Mouse Liver - Zhiying Chen; Stephen R. Yant; Cheng-Yi He; Leonard Meuse; Shiliang Shen; Mark A. Kay (2001)
The short duration of transgene expression remains a major obstacle for the implementation of nonviral DNA vectors in clinical gene therapy trials. Here, we demonstrate stable, long-term transgene expression in vivo by transfecting a linear DNA expression cassette (LDNA) into mouse liver. Interestingly, despite similar quantities and cellular distribution of injected DNAs in their livers, mice receiving LDNA encoding human α1-antitrypsin (hAAT) expressed approximately 10- to 100-fold more serum hAAT than mice injected with closed circular (cc) DNA for a period of 9 months (length of study). Furthermore, when a linear human factor IX expression cassette was delivered to factor IX-deficient mice, sustained serum concentrations of more than 4 μg/ml (80% of normal) of the human clotting factor and correction of the bleeding diathesis were obtained. Southern blot analyses indicate that, unlike ccDNA, LDNA rapidly formed large, unintegrated concatemers in vivo, suggesting that transgene persistence from plasmid-based vectors was influenced by the structure of the vector in transfected cells. No differences in transgene expression or DNA molecular structures were observed when AAV ITRs were included to flank the hAAT expression cassette in both ccDNA- and LDNA-treated animals. Linear DNA transfection provides an approach for achieving long-term expression of a transgene in vivo.